Ethical Issues Related to Low Performance Among Saudi Students in the Trends in International Mathematics and Science Study (TIMSS) - Almazroo, Noha Ali (Journal of Curriculum and Teaching Methodology, 2024)
Education represents one of the central processes of human life. Ethics, currently, has a significant role in all aspects of life. Therefore, ethics is considered as one of the main components of any teaching process all over the world. Teachers are responsible for the education and culture of the new generation; therefore, they have to act as role models to protect the discipline, culture, and honour of the school without compromising educational goals. Therefore, it is clear that ethics could be considered an integral part of a teaching career. This paper aims to reveal the reasons behind low achievement in the TIMSS tests among Saudi students and to propose ways to overcome such a problem. Analysis of the available literature showed that the main reasons behind student’s low achievement in TIMSS tests in Saudi Arabia could be attributed to several reasons including Lack of self-efficacy in teachers, Lack of teachers’ quality, Lack of differentiation methods in teaching, and Lack of knowledge to employ technology. Solutions to enhance student’s accomplishments in such examinations are suggested and explained. The solutions include that teachers must be willing to participate in school decision-making, create an appropriate learning environment, actively contribute to the implementation of the school curriculum, use effective educational strategies, engage in continuous professional development, and activate professional communities. Further research is needed to examine these points in detail and suggest successful ways to be applied to improve these areas.
Keywords: Teaching Ethics; TIMSS; Educational Issues